Dertig jaar (1975-2005) internasionale aksie vir Christelike hoër onderwys: enkele persoonlike indrukke - Walt, Barend Johannes van der (Koers, 2005)
Thirty years (1975-2005) international action for Christian higher education: a few personal reflections These personal reflections are written in view and commemoration of the fact that thirty years ago (9-13 September 1975) the formerly Potchefstroom University for Christian Higher Education (today the Potchefstroom campus of the North-West University) manifested farsightedness when it planned and received the First International Conference of Reformed Institutions for Christian Higher Education. The aim of this article is to answer the following three questions: Firstly, how did this initiative develop? (a historical review); secondly, what was the harvest of the past thirty years? (a brief evaluation); and thirdly what can be expected from the future?